The editorial process of the first Italian editions of "Tristram Shandy": Formiggini (1922) and Einaudi (1958) (Prassi Ecdotiche della Modernità Letteraria, 2019)
This paper retraces, through the examination of archive documents, the publishing process of the two first Italian editions of Laurence Sterne’s Tristram Shandy: the edition published by Formiggini in the collection «Classici del Ridere» (1922) and the one published by Einaudi in the collection «Narratori Stranieri Tradotti» (1958), which includes a famous foreword by Carlo Levi. The last chapter examines two recent editions of Sterne’s novel: the one by London-based publisher Visual Editions (2010) and the critical edition published by Mondadori in the «Meridiani» collection.
Keywords: Laurence Sterne; Tristram Shandy; Formiggini; Einaudi; Classici del ridere; Narratori Stranieri Tradotti; translation; publishing; history of publishing; editorial processes; editorial policies; Carlo Levi